Oz the great and powerful [videorecording (DVD)] - Raimi, Sam; Weisz, Rachel, 1970-; Franco, James, 1978-; Williams, Michelle, 1980-; Kunis, Mila, 1983-; Braff, Zach, 1975- (Distributed by Buena Vista Home Entertainment, 2013)
Disney's fantastical adventure Oz The Great And Powerful, from the director of the Spider-Man trilogy, follows Oscar Diggs, a small-time circus magician with dubious ethics. When Diggs is hurled away to the vibrant Land of Oz, he thinks he's hit the jackpot--until he meets three witches who aren't convinced he's the great wizard everyone's expecting. Reluctantly drawn into epic problems facing Oz and its inhabitants, Oscar must find out who is good and who is evil before it's too late. Putting his magical arts to use through illusion, ingenuity--and even some wizardry--Oscar transforms himself into the great wizard and a better man as well.